Innovative Approaches to Audit Education and Pedagogy - Wahyuni, Wahyuni; Amalia, Salsa Melsa Riski; Wahyuningsi, Arida Putri; Ramadhan, Afdatul; Khairun, Nurul Nadia (Center of Economic Students Journal, 2024)
The study aims to explore innovative approaches in audit education and their implications for student learning outcomes and professional development. A comprehensive literature review elucidates the integration of technology-enabled learning environments, active learning strategies, and experiential learning opportunities in audit curricula. The research design involves a systematic review of existing studies to identify key findings and trends in innovative pedagogies within audit education. Findings reveal the transformative potential of technology-enabled learning environments in bridging the gap between theory and practice, fostering more profound understanding, and enhancing student engagement. Active learning strategies, such as case studies and problem-based learning, promote critical thinking and teamwork among students, while experiential learning opportunities, including internships, provide hands-on experience in real-world audit engagements. The implications of these findings underscore the importance of faculty development programs, collaboration between academia and industry, and continuous curriculum updates to ensure the relevance and effectiveness of audit education. The study contributes to theory and practice by providing insights into effective pedagogical strategies and fostering a dynamic and responsive learning environment in audit education.